Layered manganese phosphorus trisulfides for high‐performance lithium‐ion batteries and the storage mechanism - Shen, Hailin; Cai, Yueling; Ma, Zhongtao; Wang, Peng; Guo, Bingkun; Cheng, Jipeng; Li, Qianqian; Wang, Hongtao; Liu, Zhongyuan; Nie, Anmin; Wu, Jinsong (Carbon energy, 2023)
Although advanced anode materials for the lithium‐ion battery have been investigated for decades, a reliable, high‐capacity, and durable material that can enable a fast charge remains elusive. Herein, we report that a metal phosphorous trichalcogenide of MnPS3 (manganese phosphorus trisulfide), endowed with a unique and layered van der Waals structure, is highly beneficial for the fast insertion/extraction of alkali metal ions and can facilitate changes in the buffer volume during cycles with robust structural stability. The few‐layered MnPS3 anodes displayed the desirable specific capacity and excellent rate chargeability owing to their good electronic and ionic conductivities. When assembled as a half‐cell lithium‐ion battery, a high reversible capacity of 380 mA h g−1 was maintained by the MnPS3 after 3000 cycles at a high current density of 4 A g−1, with a capacity retention of close to or above 100%. In full‐cell testing, a reversible capacity of 450 mA h g−1 after 200 cycles was maintained as well. The results of in‐situ TEM revealed that MnPS3 nanoflakes maintained a high structural integrity without exhibiting any pulverization after undergoing large volumetric expansion for the insertion of a large number of lithium ions. Their kinetics of lithium‐ion diffusion, stable structure, and high pseudocapacitance contributed to their comprehensive performance, for example, a high specific capacity, rapid charge–discharge, and long cyclability. MnPS3 is thus an efficient anode for the next generation of batteries with a fast charge/discharge capability. The MnPS3, endowed with a unique van der Waals structure, is highly beneficial for fast ionic insertion/extraction and can facilitate buffering volume changes during cycles with robust structural stability. A desirable reversible capacity was maintained well after long cycles in both half‐ and full‐cell lithium‐ion batteries, which is considered an efficient anode for fast charge/discharge batteries.